Uso de plantas como alimento por monos aulladores, Alouatta palliata, en el parque Yumká, Tabasco, México - del Valle, Yasminda García; Muñoz, David; Magaña-Alejandro, Miguel; Estrada, Alejandro; Franco, Berenice (Neotropical Primates, 2001)
No abstract